The Effect Of Termite Baiting On The Ecology And Genetic Structure Of Coptotermes Gestroi Population - M Vellupillai, Naveeta (2024)
Coptotermes gestroi is a prevalent subterranean termite pest known for significant ecological and economic consequences on infrastructure and cultivated crops worldwide. The efficacy of baits with chlorfluazuron, a type of Chitin Synthesis Inhibitor (CSI), as an active ingredient has been tested against the Coptotermes gestroi termites and progressive cessation of termite activity has been established. However, limited studies are available on baiting treatment effect on the genetic structure of subterranean termites. Therefore, this study investigated the breeding pattern and genetic structure of Coptotermes gestroi pre and post-baiting treatment with chlorfluazuron bait was investigated.